1993
DOI: 10.1159/000133452
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aphidicolin-induced chromosome fragility in the domestic pig (<i>Sus scrofa</i>)

Abstract: Aphidicolin (APC)-sensitive fragile sites were identified in chromosome preparations from peripheral lymphocyte cultures of 12 four-way crossbred pigs. A χ2 analysis demonstrated that aphidicolin-induced breakage events and previously reported in vivochromosome rearrangement events were not independent. Comparison of expected Poisson and negative binomial distributions to observed breakage patterns indicated that the negative binomial distribution provided a better fit to experimental data. The nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 6 publications
4
23
1
Order By: Relevance
“…The 13q4.1 fragile site was stated to be involved in the two different translocations -(6; 13) and (13; 17) related to decreased prolificacy (Kuokkanen and Mäkinen, 1998;Pinton et al, 2000). Furthermore, the results obtained showed the 5-AZA-and BrdU-sensitive Xq2.2 unstable region to be coincident with the APC-dependent site that in our previous experiment was ascertained to have been highly fragile in subfertile sows (Riggs et al, 1993;Danielak-Czech and Słota, 2002). The described chromosome fragility is suggested to increase frequency of animals with reproductive inefficiency in pig herds.…”
Section: Discussionmentioning
confidence: 59%
“…The 13q4.1 fragile site was stated to be involved in the two different translocations -(6; 13) and (13; 17) related to decreased prolificacy (Kuokkanen and Mäkinen, 1998;Pinton et al, 2000). Furthermore, the results obtained showed the 5-AZA-and BrdU-sensitive Xq2.2 unstable region to be coincident with the APC-dependent site that in our previous experiment was ascertained to have been highly fragile in subfertile sows (Riggs et al, 1993;Danielak-Czech and Słota, 2002). The described chromosome fragility is suggested to increase frequency of animals with reproductive inefficiency in pig herds.…”
Section: Discussionmentioning
confidence: 59%
“…Cytogenetic analysis in pigs has shown that the number of fragile sites varies with different animals, suggesting an animal effect in the case of APC induced fragile sites [12]. In our case, a higher number of animals and metaphase spreads will be needed to better understand the effect of aphidicolin on cattle lymphocyte cultures.…”
Section: Discussionmentioning
confidence: 76%
“…APC is a diterpenoid mycotoxin, which specifically inhibits eukaryotic DNA polymerase alpha and beta [15]. APC induced fragile sites are well documented in humans but have been studied only sporadically in mammals and domestic animals, mainly in primates, pigs, cats, and cattle [4,6,9,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several changes were made, but total correspondence was not achieved (Table 1). The result of the new evaluation is shown in Fig. la-e. Due to the extensive localization of single copy genes and fragile sites now taking place (ECHARD et al 1992;JOHANSSON et al 1995;RIGGS et al 1993;YANG and LONG 1993;R~N E 1995), a high resolution standard is almost mandatory for the pig karyotype, if future confusion shall be avoided. However, a final consensus and a comprehensive high resolution model of the pig karyotype, to make GTGIGBG-and RBG-banding collaborate in one standard, seem at present difficult to obtain, and since an establishment of a future committee seems highly unlikely, data presented in Fig.…”
Section: The Karyotype Of the Pig 167mentioning
confidence: 99%